Emotional profile of learners in self-isolation period - Kurmangaliyeva, Zhanargul; Nagymzhanova, Karakat; Zhantikeyev, Serik; Nuradinov, Almat (International Journal of Evaluation and Research in Education (IJERE), 2025)
The purpose of the study was to identify the main factors affecting the emotional state of students in self-isolation. The study was carried out surveys of students of L.N. Gumilyov Eurasian National University. As a result of the study, it was found that the COVID-19 pandemic significantly affected students, causing them stress, anxiety and loneliness due to forced self-isolation and transition to distance learning. The study found that strong family relationships, friend support, and lecturer attention positively impacted students’ stress levels, loneliness, and emotional well-being. The conducted study also revealed that learning factors such as study load, ways of learning and degree of self-efficacy play an important role in students’ emotional well-being. A survey of students revealed that they used various methods of emotional self-regulation such as meditation, breathing exercises, sports and creative activities.